Concerning the chiral phase transition in QED - Montero, J. C.; Pleitez, V. [UNESP] (American Physical Society (APS), 1990)
Using the effective potential for composite operators but without using a variational approach, we show the possible existence of a dynamical phase transition from a massive phase to a massless one. © 1990 The American Physical Society.